2011
DOI: 10.15835/nsb346230
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Arbuscular Mycorrhizal Fungi on Growth and Antioxidant Activity in Gmelina arborea Roxb. under Salt Stress Condition

Abstract: Gmelina arborea Roxb. is medicinally and economically important tree species were selected for study. An experiment was conducted to determine the influence of arbuscular mycorrhizal (AM) fungus Glomus fasciculatum on salt stress tolerance of tree species Gmelina arborea. Mycorrhizal and nonmycorrhizal seedlings were treated with 100 mM and 200 mM concentration of NaCl. G. fasciculatum treated plant showed increase in fresh and dry weight, greater percentage of mycorrhizal colonization, higher accumulation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 49 publications
0
10
0
Order By: Relevance
“…Proline accumulation was also found to be increased in control plants with increasing salinity. Dudhane et al (2011) suggest that proline accumulation in both non-mycorrhizal and mycorrhizal plants increased significantly by increasing salinity. Rabie and Almadini (2005) also reported increasing salinity level resulted in an increase of the proline concentrations in both AM plants and non-AM plants, when compared to AM plants, non-AM plants had a higher proline concentration especially at high level of salinity.…”
Section: Role Of Proline In Salinity Tolerancementioning
confidence: 89%
See 1 more Smart Citation
“…Proline accumulation was also found to be increased in control plants with increasing salinity. Dudhane et al (2011) suggest that proline accumulation in both non-mycorrhizal and mycorrhizal plants increased significantly by increasing salinity. Rabie and Almadini (2005) also reported increasing salinity level resulted in an increase of the proline concentrations in both AM plants and non-AM plants, when compared to AM plants, non-AM plants had a higher proline concentration especially at high level of salinity.…”
Section: Role Of Proline In Salinity Tolerancementioning
confidence: 89%
“…Alternatively, there are also reports which show that AMF inoculation considerably decreased proline accumulation ( Wu and Xia, 2006 ; Sheng et al, 2008 ; Borde et al, 2011 ; Echeverria et al, 2013 ) while sufficient data demonstrate the increase ( Jindal et al, 1993 ; Jahromi et al, 2008 ; Elhindi et al, 2017 ). On the contrary, some studies also indicate a null effect on proline accumulation ( Dudhane et al, 2011 ; Estrada et al, 2013 ) (Table 1 ). According to Ruiz-Lozano et al (1996a) , mycorrhizal plants are lower in proline accumulation (except F. mosseae colonized plants) than those of non-mycorrhizal plants.…”
Section: Role Of Proline In Salinity Tolerancementioning
confidence: 99%
“…In a saline environment, root growth is delayed with the effect of salt on cell toxicity and due to low soil water potential ( Psarras et al, 2008 ). An increase in salt concentrations proportionately increases the mycorrhizal response in Sesbania and Gmelina plants ( Giri and Mukerji, 2004 ; Dudhane et al, 2011 ). We also observed salinity-level variations in the mycorrhizal symbiosis of C 3 and C 4 plants.…”
Section: Discussionmentioning
confidence: 99%
“…This can restrain AMF spore germination, colonization capacity, and hyphal development [13]. However, many researchers have reported that AMF can enhance the ability of plants to cope with salinity [14]- [20], leading to improved growth and productivity under saline conditions [21] [22] [15] [17]. The benefits of symbiosis under saline conditions include increased nutrient uptake compared with plants without mycorrhizal associations, accumulation of compounds regulating osmotic adjustment in the roots, and increase in photosynthesis and water use efficiency [14] [23].…”
Section: Introductionmentioning
confidence: 99%